La representació de les palatals - Palmada, Blanca (Caplletra. Revista Internacional de Filologia, 1995)
The benefits of a Complex Segment representation for palatals have been considered in the light of gliding processes which turn these consonants into glides. Gliding processes have sometimes been described as «destridentization» and «delateralization». But this view gives no explanation of why vocalization is restricted to sorne segments, and plain stridents and laterals do not suffer from it. I have examined gliding processes affecting stridents and laterals to show that a solution based on Feature Geometry is required. The crucial observation is that every speech sound must have a major articulator, and that this constraint applies along the phonological derivation. Since Coronal is the unmarked specification for Place, its presence crucially depends on that of its subordinate features, Strident and Lateral. In this way, if a rule removes Strident or Lateral from the representation, Coronal will also be lost. Consequently, the remaining Dorsal articulator is interpreted as Primary, resulting in a glide. My paper has focused on two cases that involve the delinking of a dependent of Coronal in Majorcan Catalan.